Elementary statistics - Weiss, N. A. (Addison-Wesley, 1996)
This introduction to statistical research and evaluation explains statistical concepts and procedures, and the logic behind them. Real examples and data sets are used, and traditional presentation of topics is integrated with technology and the techniques of data analysis, including Minitab.